Chemical Vapor Deposition Grown Monolayer Graphene Microsensors with RF Ring Oscillator Backend Circuit - Tawfik, Mohamed Ahmed Waheed (AUC Knowledge Fountain, 2023)
This work presents the integration of a backend RF ring oscillator readout circuit to transduce structural changes in CVD-grown monolayer graphene into an electrical signal and the implementation of it to detect physical changes such as radiation and flexural strain. The novelty in this work lies in the following (1) the ability of the sensor platform to overcome environmental effects, such as light photons and temperature changes, through the readout circuit, and (2) it opens the door for the scalability of CVD-grown graphene-based for sensors and devices. Thus, the introduced sensors solve several downsides in the state-of-the-art graphene-based radiation and strain devices, such as dependency on high atomic number, fading signal problems, dependency on electron excitation to generate a signal, difficulties in fabrication of single crystals, structural instabilities due to fabrication, and toxicity of high atomic number sensing elements. In our first implementation, we introduce a new radiation detection approach by measuring the change in resistance in correlation with the incident irradiation dose. This approach solves several of the problems reported in the literature by eliminating the necessity of structural stability or fabrication imperfections, avoiding bulk volumes regarding the sensing element's geometry, and avoiding fading signal problems. Unlike traditional radiation sensors, cooling is not needed as the resolution is determined mainly by the level of structural damage, instead of the generated carriers due to incident radiation, with no toxicity problems as carbon-based materials are to be used. Sensitivity in gamma radiation detection of 7.86 was measured in response to cumulative gamma radiation dose ranging from 0 to 1 kGy which is suitable in food industry applications and homeland security. Senstivity of the platform to Beta was 27 times lower than gamma due to lower energy of gamma irradiation than that of beta irradiation. The new approach helps in minimizing background environmental effects (e.g., due to light and temperature), leading to an insignificant error in the output change in frequency of the order of 0.46% when operated in light versus dark conditions. The uncertainty in readings due to background light was calculated to be in the order of 1.34 Ω, which confirms the high stability and selectivity of the proposed sensor under different background effects. Our second implementation used the same platform on a flexible substrate as a new approach to detect flexural strain. This was achieved by dependency on the structure deformation method to overcome the limitations of the other mechanisms, such as low flexural strain sensitivity and lower gauge factors at low strain levels. Unlike traditional metal-foil strain sensors, the simple fabrication avoids structural damage in the monolayer graphene sheet. The sensor platform is also marked by having high flexibility and high conductivity combined with a high signal-to-noise ratio, with no need for calibration merged with high flexural sensitivity as monolayer graphene hinders creation of conductivity channels through straining. Our flexural strain sensor has a gauge factor of 64.36, corresponding to a change in frequency of 7.42%, achieving a sensitivity of around three times higher than sensors in literature working in the same strain range.